Disposition of intravenously or orally administered silver nanoparticles in pregnant rats and the effect on the biochemical profile in urine. Issue 5 (3rd October 2016) - Fennell, Timothy R.; Mortensen, Ninell P.; Black, Sherry R.; Snyder, Rodney W.; Levine, Keith E.; Poitras, Eric; Harrington, James M.; Wingard, Christopher J.; Holland, Nathan A.; Pathmasiri, Wimal; Sumner, Susan C. J.
Abstract: Few investigations have been conducted on the disposition and fate of silver nanoparticles (AgNP) in pregnancy. The distribution of a single dose of polyvinylpyrrolidone (PVP)‐stabilized AgNP was investigated in pregnant rats. Two sizes of AgNP, 20 and 110 nm, and silver acetate (AgAc) were used to investigate the role of AgNP diameter and particle dissolution in tissue distribution, internal dose and persistence. Dams were administered AgNP or AgAc intravenously (i.v.) (1 mg kg −1 ) or by gavage (p.o.) (10 mg kg −1 ), or vehicle alone, on gestation day 18 and euthanized at 24 or 48 h post‐exposure. The silver concentration in tissues was measured using inductively‐coupled plasma mass spectrometry. The distribution of silver in dams was influenced by route of administration and AgNP size. The highest concentration of silver (μg Ag g −1 tissue) at 48 h was found in the spleen for i.v. administered AgNP, and in the lungs for AgAc. At 48 h after p.o. administration of AgNP, the highest concentration was measured in the cecum and large intestine, and for AgAc in the placenta. Silver was detected in placenta and fetuses for all groups. Markers of cardiovascular injury, oxidative stress marker, cytokines and chemokines were not significantly elevated in exposed dams compared to vehicle‐dosed control. NMR metabolomics analysis of urine indicated that AgNP and AgAc exposure impact the carbohydrate, and amino acid metabolism. This study demonstrates that silver crosses the placenta and is transferred to the fetus regardless of the form of silver. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Here is presented a comprehensive investigation of the distribution of polyvinylpyrrolidone (PVP)‐stabilized AgNP (20 or 110 nm) in pregnant rats after a single injection or oral gavage dose. The biological impacts of AgNP exposure were evaluated by metabolomic analysis, and measurement of biomarkers of cardiovascular injury, oxidative stress and inflammation. The investigation provided a basic understanding of the distribution, internal dose, persistence, metabolomics and elimination of AgNP after exposure in pregnant rats.